Respon Pertumbuhan Dan Hasil Tanaman Kacang Tanah terhadap Pemberian Berbagai Dosis POC Sabut Kelapa dan Batang Pisang di Lahan Rawa Lebak - Ellisa Rusiani; Mahdiannoor; Farida Adriani (Rawa Sains: Jurnal Sains STIPER Amuntai, 2018)
Peanuts is a herbs plants, its flowers like a butterfly and its pods at the underground. Production decrease of peanuts at the Hulu Sungai Utara Regency because chemical fertilizers are used excessively. It causes the soil isn’t loose, hard, and sour. Liquid organic fertilizer (LOF) of coconut husk and banana trunk have many nutrients like nitrogen, phosphorus, and potassium. This study aims to (i) determine the growth and yield response of peanut to the application liquid organic fertilizer of coconut husk and banana trunk on lebak wetlands, (ii) determine the best dosage liquid organic fertilizer of coconut husk and banana trunk growth and yield of peanut in lebak wetlands. It used a randomized block design (RBD). The results showed that application liquid organic fertilizer of coconut husk and banana trunk had significant effect on plant height and number of leaves age 28 day after planting (DAP) and no effect on plant height and number of leaves age 14 and 21 DAP, age of the plant when the first flowering, number of pods and plant fresh weight of pods. p3 (250 ml) was the best dosage to growth and yield of peanut.